Testing Effect Of Immunomodulator Ethanol Extract Of Mengkudu Leaves (Morinda Citrifolia) On Macrofag Cell Activities In Mencit Balb/C Infected Plasmodium Berghei - Jon Farizal; Leni Marlina; Susiwati Susiwati; zamharira Muslim (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
Background malaria fever is a disease that is still a problem in developing countries. Plasmodium bergheiis a facultative intracellular parasite, so the immune system that plays a role is the cellular system. Morinda citrifolia is a traditional medicinal plant that contains many active compounds that can reduce the number of malaria parasitemia. Proving the immunomodulatory effect of ethanol extract ofmorinda citrifolia on phagocytosis activity of Balb/c mice infected with Plasmodium berghei. The data were obtained from calculating the number of phagocytosis activity of macrophage cells in each field of view. A different test for macrophage phagocytosis using One Way ANOVA followed by Post Hoct Test. Method this type of research is experimental with the design of the post-test only control group design in experimental animals balb/c mice consisting of 24 male mice, divided into 4 groups. (K) is the control group given Aquabidest, and the treatment group (P1, P2, P3) which was given extract morinda citrifolia with stratified doses (0.64 mg / kgBb / day, 1.28 mg / kgBb / day, 2.56 mg / kgBb / day). The treatment process was given for 13 days and on the 6th day was infected with Plasmodium bergheias much as 0.1 ml x 106 intraperitoneally. On the 14th day, peritoneal fluid isolation was carried out followed by an examination of macrophage cell phagocytosis activity. Result ethanol extract Morinda citrifolia can increase macrophage phagocytosis, between control and treatment P1, P2, and P3 have significant differences, but between treatments, there is no significant difference. Conclusion. Ethanol extract of Morinda citrifolia in various doses can increase the phagocytosis of macrophages in Babl/c mice infected with Plasmodium berghei.